1998
DOI: 10.1144/gsjgs.155.4.0697
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical and Sr–Nd–Pb isotopic data bearing on the origin of Pan-Africangranitoids in the Kid area, southeast Sinai, Egypt

Abstract: The Kid plutonic suite in southeast Sinai, Egypt is composed of: (1) a gabbro–diorite complex; (2) quartz monzodiorite; (3) granodiorite–monzogranite association; (4) syenogranite. Major- and traceelement analyses and radiogenic isotope data (Rb/Sr, Sm/Nd and Pb/Pb) are presented for these rocks. Rb–Sr isochrons indicate ages of 581±11 Ma, 576±11 Ma and 570±4 Ma for the quartz monzodiorite–granodiorite–monzogranite association and syenogranite, respectively. The gabbro–diorite complex is a layered intrusion va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(51 citation statements)
references
References 60 publications
4
47
0
Order By: Relevance
“…Sr i and eNd(T) calculated for the Kid schist over the age range of 800-640 Ma vary from 0.6981 to 0.7028 and ?3.8 to ?2.6, respectively. eNd(T) values calculated for all rocks for the Figure 4 shows an eNd(T) versus age diagram, where results of the present study are plotted along with data from the literature (Azer et al 2009;Beyth et al 1994;Katzir et al 2007a, b;Moghazi et al 1998;Mushkin et al 2003;Stein and Goldstein 1996). The 820-740 Ma rocks of the northernmost ANS define a restricted eNd(T) field, which falls slightly below the DM evolution curve of DePaolo (1981).…”
Section: Whole-rock Sr-nd Isotope Resultsmentioning
confidence: 57%
See 4 more Smart Citations
“…Sr i and eNd(T) calculated for the Kid schist over the age range of 800-640 Ma vary from 0.6981 to 0.7028 and ?3.8 to ?2.6, respectively. eNd(T) values calculated for all rocks for the Figure 4 shows an eNd(T) versus age diagram, where results of the present study are plotted along with data from the literature (Azer et al 2009;Beyth et al 1994;Katzir et al 2007a, b;Moghazi et al 1998;Mushkin et al 2003;Stein and Goldstein 1996). The 820-740 Ma rocks of the northernmost ANS define a restricted eNd(T) field, which falls slightly below the DM evolution curve of DePaolo (1981).…”
Section: Whole-rock Sr-nd Isotope Resultsmentioning
confidence: 57%
“…A Sr i locality map including data from this study and the literature (Azer et al 2009;Beyth et al 1994;Katzir et al 2007a, b;Moghazi et al 1998;Mushkin et al 2003;Stein and Goldstein 1996;Stern and Manton 1987) is shown in Fig. 3c.…”
Section: Whole-rock Sr-nd Isotope Resultsmentioning
confidence: 71%
See 3 more Smart Citations